SIMULATION AND PERFORMANCE ANALYSIS OF ROUTING PROTOCOLS FSR AND ZRP IN VEHICULAR AD-HOC NETWORK (VANET) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Vehicular Ad-Hoc Network (VANET) is a wireless routing network which used ad hoc network system as the basis. VANET was formed to give solution to the unclear network infrastructure or frequently changing network topology. The change of speed and the nodes amount in an area influenced the overhead level in sending message and end to end delay with low packet loss. The right routing protocol selection has an important role in guarantee the Quality of Service in VANET which needs low delay and overhead. This study analyzed the Fisheye State Routing (FSR) protocol performance as a proactive routing protocol that renew the table routing in certain period and Zone Routing Protocol (ZRP) as a hybrid protocol that uses zone and hop distant to decide the table routing renewal in sending data with Cisco codec G 711 standard in highway areas using NS-2.31 and NS-2.35 and traffic simulator SUMO 0.12.3. Moreover, the measured metrics performances were Average end-to-end delay, Normalized Routing Load, Average Throughput, Packet Delivery Ratio (PDR), and Routing Overhead.